2017
DOI: 10.1634/theoncologist.2017-0337
|View full text |Cite
|
Sign up to set email alerts
|

Portomesenteric Venous Stenting for Palliation of Ascites and Variceal Bleeding Caused by Prehepatic Portal Hypertension

Abstract: Portomesenteric venous stenosis is a challenging complication of pancreaticobiliary malignancy. Portomesenteric stenoses can lead to esophageal, gastric, and mesenteric variceal bleeding, as well as abdominal ascites. The purpose of this study was to evaluate the safety and efficacy of portal vein stenting (PVS) in patients with cancer who have symptomatic portal hypertension caused by portomesenteric venous compression. As a low-risk procedure with a high clinical success rate, PVS can play a substantial role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The placement of a 10-mm-diameter, 27-mm-long noncovered stent (not shown) in the MPV resulted in a pressure gradient of 2 mm Hg. high technical and clinical success in the setting of PV stenosis after organ transplantation and for palliation in the setting of extrinsic malignant compression of the PV (19)(20)(21)(22). However, there are fewer data on the outcomes of PMV venoplasty and stent placement following pancreatic surgery in this era of expanding neoadjuvant and adjuvant oncologic therapies and major vascular reconstruction (21,23,24).…”
Section: Percutaneous Pmv Interventionmentioning
confidence: 99%
“…The placement of a 10-mm-diameter, 27-mm-long noncovered stent (not shown) in the MPV resulted in a pressure gradient of 2 mm Hg. high technical and clinical success in the setting of PV stenosis after organ transplantation and for palliation in the setting of extrinsic malignant compression of the PV (19)(20)(21)(22). However, there are fewer data on the outcomes of PMV venoplasty and stent placement following pancreatic surgery in this era of expanding neoadjuvant and adjuvant oncologic therapies and major vascular reconstruction (21,23,24).…”
Section: Percutaneous Pmv Interventionmentioning
confidence: 99%
“…The use of anticoagulant and antiplatelet agents remains controversial because they increase the risk of variceal bleeding and coagulopathy in many patients. Physicians favor the use of these agents because recanalization of thrombotic occlusion is technically challenging [ 5 7 ]. A stratified randomized, controlled study is needed to further evaluate the benefits of using anticoagulant and antiplatelet agents.…”
Section: Discussionmentioning
confidence: 99%
“…Portal hypertension can present as ascites, congestive enteropathy, variceal bleeding, or hypersplenism [ 3 ]. PV stents are usually inserted to relieve portal hypertension in symptomatic patients, and several studies have demonstrated their effect [ 3 4 5 ]. Because cavernous transformation followed by PV occlusion could preserve the function of the liver in non-oncologic patients, the importance of the PV flow may be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulation regimen was determined based upon the patient’s history of atrial fibrillation, rather than maintenance of splenic stent patency and likely would have consisted of a less aggressive regimen in the absence of this history. There are no standardized guidelines regarding anticoagulation after portomesenteric stenting, and some studies have failed to find an association between type of anticoagulation and risk of stent thrombosis (Sheth et al 2018 ). At 6 months follow-up, the patient remained free of abdominal ascites.…”
Section: Discussionmentioning
confidence: 99%